Education for Peace: Transforming Individuals for a Peaceful World (Journal of Advances and Scholarly Researches in Allied Education, 2018)
It is the individual who is responsible for all the problems in the world. He is the creator of all panics, miseries, confusions and sorrows in the present world. So, to transform the world in to a better place to live, the process should begin from the individuals. In the present time violence is increasing rapidly in human being. If we look at the world today we feel frustrated and even fearful to see the types of violent acts done by man. Today man is living in an era of unprecedented violence, in the world of international terrorism and warfare, crime, injustice, harassment and exploitation. Thus ‘peace’ in the world is possible if and only if each individual is transformed into a peaceful human being. In present era, education is the only way by which peace and moral values can be inculcate by providing value education to the children. We proudly announce that India is always a peace loving country. This love for peace, which is in our blood and is inherited from our ancestors, has survived in our hearts, and is active even today. The present paper is about the education for peace. It focuses on the meaning of peace, peace education, aims of peace education, scope of peace education, historical background of peace education, role of school and teacher for promoting peace education and methods of teaching of peace education.